2016
DOI: 10.1002/oby.21423
|View full text |Cite
|
Sign up to set email alerts
|

From last supper to self‐initiated weight loss: Pretreatment weight change may be more important than previously thought

Abstract: Objective Evaluate the association between pre-treatment and during-treatment weight change. Evaluate differences in self-regulation between those who gain weight, remain weight stable, and lose weight pre-treatment. Methods Data from the first six months of a behavioral weight loss study were used. Participants (n=283) were weighed at two assessment points (screening visit and baseline) prior to the start of treatment and at every treatment session. Participants were divided into those who gained weight, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(62 citation statements)
references
References 24 publications
8
46
8
Order By: Relevance
“…In contrast to an initial report (West et al, ), this is the second study to report no significant relationship between The Last Supper and weight loss outcomes (Kerrigan et al, ). The current data, in combination with the previous two last supper studies (West et al, ), highlight the importance of obtaining a true pre‐treatment weight at the first treatment appointment as individuals' weight can change dramatically between their initial screening/assessment appointment and when they actually start treatment (Kerrigan et al, ). Similarly, despite current participants reporting a wide range of Weight Suppression (0 to −92 pounds) and Pretreatment Weight Trajectories (from 37 pounds lost to 99 pounds gained in the year preceding treatment), neither variable was related to weight loss outcomes.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In contrast to an initial report (West et al, ), this is the second study to report no significant relationship between The Last Supper and weight loss outcomes (Kerrigan et al, ). The current data, in combination with the previous two last supper studies (West et al, ), highlight the importance of obtaining a true pre‐treatment weight at the first treatment appointment as individuals' weight can change dramatically between their initial screening/assessment appointment and when they actually start treatment (Kerrigan et al, ). Similarly, despite current participants reporting a wide range of Weight Suppression (0 to −92 pounds) and Pretreatment Weight Trajectories (from 37 pounds lost to 99 pounds gained in the year preceding treatment), neither variable was related to weight loss outcomes.…”
Section: Discussioncontrasting
confidence: 70%
“…Even very early treatment nonadherence may be a signal for changing weight loss treatment approach (Unick et al, 2015). In contrast to an initial report (West et al, 2011), this is the second study to report no significant relationship between The Last Supper and weight loss outcomes (Kerrigan et al, 2016). The current data, in combination with the previous two last supper studies (West et al, 2011), highlight the importance of obtaining a true pre-treatment weight at the first treatment appointment as individuals' weight can change dramatically between their initial screening/assessment appointment and when they actually start treatment (Kerrigan et al, 2016).…”
Section: Weight Loss-subsequentmentioning
confidence: 59%
See 2 more Smart Citations
“…Three previous studies found that many participants experienced significant pretreatment weight change, between the initial screening visit (SV) and first baseline visit (BV), before beginning behavioral weight loss interventions [1,2,3]. Importantly, one study indicated that pretreatment weight change was associated with in-treatment outcomes [2].…”
Section: Background Weight Loss Interventionmentioning
confidence: 99%